CT-guided joint cavity release for postpartum sacroiliac joint pain management: an evaluation of its efficacy, safety, and clinical outcomes - Mao-jiang, Yang; Xian, Qiong; Bhetuwal, Anup; Bing, Li; Xiao-xue, Xu (Frontiers in Medicine, 2024)
The central aim of this study was to evaluate the safety and effectiveness of Computed Tomography (CT)-guided joint cavity release in treating patients suffering from postpartum sacroiliac joint pain.A retrospective analysis was conducted on a sample of 37 patients who presented with postpartum sacroiliac joint pain and underwent CT-guided sacroiliac joint release treatment atThe Affiliated Hospital of North Sichuan Medical College. General clinical attributes of the patients were recorded, and the intensity of their pain before and after the operation was compared using the Numeric Pain Rating Scale (NRS). The effectiveness of the surgical treatment was assessed using the Modified MacNab criteria. The functional status of the sacroiliac joint at 3-and 6-month intervals post-operation was examined, and any complications related to surgery were documented.The follow-up period was completed by all patients, with the successful implementation of CT-guided unilateral/bilateral sacroiliac joint release undertaken in 37 patients. Patient reported pain, as measured by the Numeric Pain Rating Scale (NRS), was considerably reduced postoperatively with scores showing significant decrement from 7.14 ± 1.23 preoperatively to 1.26 ± 0.53 at 1 week, 1.86 ± 0.62 at 1 month, 1.92 ± 0.48 at 3 months, and 1.97 ± 0.61 at 6 months postoperatively, respectively (P<0.05). The comprehensive record of treatment response rates, interpreted as excellent and good, were consistent, standing at 100% (37/37), followed by 97.30% (35/37) and concluding with 91.89% (33/37). The Oswestry Disability Index (ODI) scores reflecting the patient's perceived level of disability prior to the surgery, and at 3 and 6 month intervals post-surgery were 45.12 ± 6.01, 18.14 ± 2.23, and 14.25 ± 2.15 respectively, demonstrating a significant improvement in postoperative scores when compared with preoperative scores (P<0.05). The surgeries conducted were devoid of any complications such as bleeding, infection, cardiovascular or cerebrovascular incidents, or decline in joint functionality in any of the patients. Conclusion: Evidently, CT-guided joint cavity release presents as an effective therapeutic approach for the management of postpartum sacroiliac joint pain, enhancing quality of life and preserving patient safety.